CRAIG JEFFREY: Timepass: Youth, Class, and the Politics of Waiting in India. Stanford: Stanford University Press 2010. 221 sider. ISBN 978-0-8047- 7074-3. Pris: $ 21.95. - Nielsen, Kenneth Bo (Tidsskriftet Antropologi, 2011)
Intet resumé